Enhanced responses to tumor immunization following total body irradiation are time-dependent. - Adi Diab; Robert R Jenq; Gabrielle A Rizzuto; Adam D Cohen; Deonka W Huggins; Taha Merghoub; Manuel E Engelhorn; José A Guevara-Patiño; David Suh; Vanessa M Hubbard-Lucey; Adam A Kochman; Suzie Chen; et al. (PLoS ONE, 2013)
The development of successful cancer vaccines is contingent on the ability to induce effective and persistent anti-tumor immunity against self-antigens that do not typically elicit immune responses. In this study, we examine the effects of a non-myeloablative dose of total body irradiation on the ability of tumor-naïve mice to respond to DNA vaccines against melanoma. We demonstrate that irradiation followed by lymphocyte infusion results in a dramatic increase in responsiveness to tumor vaccination, with augmentation of T cell responses to tumor antigens and tumor eradication. In irradiated mice, infused CD8(+) T cells expand in an environment that is relatively depleted in regulatory T cells, and this correlates with improved CD8(+) T cell functionality. We also observe an increase in the frequency of dendritic cells displaying an activated phenotype within lymphoid organs in the first 24 hours after irradiation. Intriguingly, both the relative decrease in regulatory T cells and increase in activated dendritic cells correspond with a brief window of augmented responsiveness to immunization. After this 24 hour window, the numbers of dendritic cells decline, as does the ability of mice to respond to immunizations. When immunizations are initiated within the period of augmented dendritic cell activation, mice develop anti-tumor responses that show increased durability as well as magnitude, and this approach leads to improved survival in experiments with mice bearing established tumors as well as in a spontaneous melanoma model. We conclude that irradiation can produce potent immune adjuvant effects independent of its ability to induce tumor ablation, and that the timing of immunization and lymphocyte infusion in the irradiated host are crucial for generating optimal anti-tumor immunity. Clinical strategies using these approaches must therefore optimize such parameters, as the correct timing of infusion and vaccination may mean the difference between an ineffective treatment and successful tumor eradication.